1995
DOI: 10.1002/depr.3050030403
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of alpha‐1‐acid glycoprotein and interleukin‐6 in refractory depression

Abstract: Plasma concentrations of alpha-1 -acid glycoprotein (AGP), C-reactive protein (CRP), interleukin-6 (IL-6), and soluble interleukin-6 receptor (sIL-6R) as well as the changes in glycosylation of AGP were measured in 60 patients with major depression hospitalized at the Deparhnent of Psychiaq, Medical Academy in Bydgomn, and in 20 age-and sex-matched controls. Thirty-four depressed patients met the criteria of refiactory depression. Patients with refiactoly depression (RD) had a longer duration of the illness an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…The results concerning the increased levels of AGP and the inflammatory patterns of AGP-RC in refractory de pressed patients, before Li addition, obtained in this study are in concordance with our previous observations on refractory depressed patients [27], In agreement with our previous study [28], we also found that treatment with Li may attenuate the abnormalities of acute-phase re sponse. After 4 weeks of Li treatment a decrement of pre viously increased levels of all APPs studied was observed as well as a decrease of the high values of AGP-RC and ACT-RC.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results concerning the increased levels of AGP and the inflammatory patterns of AGP-RC in refractory de pressed patients, before Li addition, obtained in this study are in concordance with our previous observations on refractory depressed patients [27], In agreement with our previous study [28], we also found that treatment with Li may attenuate the abnormalities of acute-phase re sponse. After 4 weeks of Li treatment a decrement of pre viously increased levels of all APPs studied was observed as well as a decrease of the high values of AGP-RC and ACT-RC.…”
Section: Discussionsupporting
confidence: 82%
“…Patients belonging to this group had a longer duration of illness and of the last depressive episode and were most refractory' to pharmacological treatment. In another study on refractory depressed patients, we have found a more intensive index of acute-phase response in these patients compared with nonrefractory ones [27], Our preliminary data of lithium effect on APPs have suggested that Li may exert a normalizing effect on both concentration and abnormal microheterogeneity of APPs [28], In view of this, we addressed the issue whether lithi um action on the APPs may be associated with the mecha nisms of its potentiation of antidepressant drugs in refrac tory depression.…”
Section: Introductionmentioning
confidence: 99%
“…Phrased differently, consideration of in vivo results is needed for a correct interpretation of ex vivo data. In this respect, it has been shown that subchronic treatment with fluoxetine, another SSRI, normalized the initially increased serum IL-6 concentrations in depressed patients (Sluzewska et al 1995a(Sluzewska et al , 1995b. In Wistar rats, an 8-week exposure to mild, unpredictable stress induces a depression-like state with an increased capacity of splenocytes to produce IL-1 and IL-2.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence for increased (1) production of pro-inflammatory cytokines such as IL-1 ␤ , IL-6 and IFN ␥ in culture supernatant of mitogen-stimulated PBMC; and (2) serum concentrations of IL-6, IL-2, and IL-2 receptor in depression (Nassberger and TraskmanBendz 1993;Maes et al 1993aMaes et al , 1993bMaes et al , 1994Sluzewska et al 1995aSluzewska et al , 1995bSluzewska et al , 1996aSluzewska et al , 1996bSeidel et al 1995Seidel et al , 1996aFrommberger et al 1997). The above cytokines are known to orchestrate the key steps in the complex network, which regulates responses in cell-mediated and humoral immunity and in the IRS (Cavaillon 1996).…”
mentioning
confidence: 99%
“…To our knowledge, only one study examined the levels of TNF-␣ in elderly women with chronic MDD and found no alterations of this cytokine (Brambilla and Maggioni 1998). In addition to these cytokines, other immune parameters, including ␣ 1-glycoprotein (AGP), have been investigated with regard to psychopathological improvement and antidepressive treatment (Frommberger et al 1997;Maes et al 1995b;McAdams 1993;Seidel et al1996;Sluzewska et al 1995b;Sluzewska et al 1996;Weizman et al 1994). The association of some of these factors (IL-6, soluble IL-6 receptor, AGP, IL-1 receptor antagonist, IL-1 ␤ ) with the depressive symptomatology points to their possible state marker character as suggested by Maes et al (1995a) and .…”
mentioning
confidence: 99%